(untitled) (Tempo e Argumento, 2024)
The article examines the recent evolution of the democratic political regime in the Latin American and Caribbean region. In theoretical terms, the text is related to studies on the quality of democracy, especially through the views proposed by Leonardo Morlino. Methodologically, the study takes an interpretation-essay style, as well as documentary analysis. Descriptive and interpretative inferences are grounded on databases and reports published by renowned research centers. Promoting democracy, preventing populism, and resisting authoritarianism are the main politico-social challenges on the continent, mainly in the global context of an autocratization wave that has prevailed since the early 21st century.